2016
DOI: 10.1016/j.apm.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of linear motion error for Hexarot parallel manipulators

Abstract: a b s t r a c tHexarot is a robotic manipulator that belongs to the family of axis symmetric parallel mechanisms. The robot is able to move the robot platform or tool center point in six degrees of freedom (DOF). This paper presents the kinematics model of the robot including the inverse and forward kinematics, and its time derivatives. Then using the kinematics formulations, investigation of the nonlinear motion of the Hexarot robot for a desired linear motion path is performed. For this purpose, the concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The kinematics, workspace, error analysis, and control of the hexarot mechanism have then been studied in different research works. [40][41][42][43] Hexarot mechanism as a parallel manipulator using six 5 DOF passive arms to manipulate an end effector has several advantages. Five DOF arm is not sensitive to torsion or bending, and it is manufactured lightweight with a high stiffness.…”
Section: Hexarot Mechanismmentioning
confidence: 99%
“…The kinematics, workspace, error analysis, and control of the hexarot mechanism have then been studied in different research works. [40][41][42][43] Hexarot mechanism as a parallel manipulator using six 5 DOF passive arms to manipulate an end effector has several advantages. Five DOF arm is not sensitive to torsion or bending, and it is manufactured lightweight with a high stiffness.…”
Section: Hexarot Mechanismmentioning
confidence: 99%
“…14,15 The parallel manipulators consist of several passive joints which are connected to each other in the close chain connection between the base and the end effector. [16][17][18] The end effector of the manipulator can reach the angular positioning limits if one of the passive joints passes the limitations without consideration of the other passive joints. 19 Nevertheless, the control of parallel manipulators is more straightforward compared with serial manipulators due to their analytical inverse kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar attempt, Chalak et al [17,18] introduced a linear interpolation of circular path for a hexapod mechanism, which adopts the median circle for approximating nonlinear error and compensates it by reducing the end effector feed rate. Moreover, Pedrammehr et al [19] investigated the modeling of linear motion error of a 6-DOF hexarot parallel mechanism by the mentioned median circle. They concluded that the increase to the longitudinal distance is the most influencing parameter on the error.…”
Section: Introductionmentioning
confidence: 99%